Handbook of Life Course Health Development 2017
DOI: 10.1007/978-3-319-47143-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Early in the Life Course: Time for Obesity Prevention

Abstract: One of the reasons for the intractability of childhood obesity is the underappreciation of the complexity and interconnectedness of contributing factors across the life course. A multilevel approach for obesity prevention takes into account individual risk factors that operate “above water” (family, neighborhood, policies) and the interaction with biology and “underwater” influences (genetics, epigenetics, physiology) and recognizes that these factors also interact across the life course, starting before birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 186 publications
(225 reference statements)
0
20
0
2
Order By: Relevance
“…Social epidemiologist Summer Sherburne Hawkins, PhD, MS, collaborated with pediatrician and prenatal nutrition expert Emily Oken, MD, MPH and pediatrician and preventive cardiology expert Matthew W. Gillman, MD, SM, to produce Early in the Life Course: Time for Obesity Prevention. This chapter adopts a multilevel approach in identifying the periods and factors that are the greatest contributors to obesity and explores how innovative research methodologies can be used to demonstrate causality (Hawkins et al 2017 (Drmic et al 2017).…”
Section: Section Iii: the Life Course Origins And Consequences Of Spementioning
confidence: 99%
“…Social epidemiologist Summer Sherburne Hawkins, PhD, MS, collaborated with pediatrician and prenatal nutrition expert Emily Oken, MD, MPH and pediatrician and preventive cardiology expert Matthew W. Gillman, MD, SM, to produce Early in the Life Course: Time for Obesity Prevention. This chapter adopts a multilevel approach in identifying the periods and factors that are the greatest contributors to obesity and explores how innovative research methodologies can be used to demonstrate causality (Hawkins et al 2017 (Drmic et al 2017).…”
Section: Section Iii: the Life Course Origins And Consequences Of Spementioning
confidence: 99%
“…Do certain key factors act as "triggers," setting in motion a cascade of future biological response patterns? Biological conditioning processes can range from the exposure to a specific nutrient like folate and its influence on epigenetic methylation based on availability in indigenous diets (see Herman and Taylor Baer 2017) to the role that different patterns of sleep and sleep duration have on cycling of neuroendocrine hormones that serve to prime other factors related to growth, metabolism, and the biological underpinning of behavioral response systems (see Mummert et al 2017;Hawkins et al 2017).…”
Section: Mechanism Researchmentioning
confidence: 99%
“…Throughout this volume, authors have highlighted the important role of intervention research for better understanding not only how to intervene, but also when. For example, the chapter by Hawkins and colleagues (Hawkins et al 2017) suggests that a key to reducing childhood obesity is finding the right level and time in the life course to intervene for the maximal effectiveness and efficiency of interventions. However, the challenge of mounting programs designed to modify obesogenic health development pathways may be quite complex, involving multiple settings (e.g., medical care, homes, child care, school) (Taveras, Blackburn, et al 2011a;Taveras, Gortmaker, et al 2011b;Taveras et al 2012), or components (e.g., system redesign, individual behavior change strategies including e-technology) (Lubans et al 2010;Taveras et al 2012), and targeting single or multiple factors (Taveras, Gortmaker, et al 2011b;Vesco et al 2012).…”
Section: Intervention Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Life course epidemiology proposes that factors during peri- and post-natal periods may influence the development of obesity from early life through adulthood [ 3 , 4 ]. Observational studies have shown that maternal smoking during pregnancy [ 5 7 ], excessive gestational weight gain [ 8 10 ], gestational diabetes mellitus (GDM) [ 11 ], and accelerated infant weight gain [ 6 , 12 , 13 ] are associated with higher risk for childhood obesity.…”
Section: Introductionmentioning
confidence: 99%